Military orders and crusades
1 online resource (402 pages).
Keywords: This volume celebrates the work and impact of Professor Helen Nicholson by bringing together twenty-two chapters by colleagues, former students and friends which focus on her major research interests: the Military Orders, women in the Middle Ages and the history of the crusades and the Latin East.These chapters develop and continue discussion that owes much to Nicholson's research contributions, which she has continued since retirement from her chair in Cardiff University in 2022. They are sorted into five parts reflecting a range of themes: everyday life of the Military Orders; women - in their royal, crusading and Military Orders contexts; the Military Orders in England and their members; aspects of warfare in the Latin East and in Europe; and new findings about the history of crusading and the Military Orders that can be derived from the careful study of archives, records and manuscript sources.This book will appeal to researchers and students interested in Medieval History, the crusades, the Military Orders and Women's History.